Diabetes in developing countries - Misra, A.; Gopalan, H.; Jayawardena, R.; Hills, A.P.; Soares, Mario; Reza-Albarrán, A.A.; Ramaiya, K.L. (WILEY, 2019)
© 2019 Ruijin Hospital, Shanghai Jiaotong University School of Medicine and John Wiley & Sons Australia, Ltd There has been a rapid escalation of type 2 diabetes (T2D) in developing countries, with varied prevalence according to rural vs urban habitat and degree of urbanization. Some ethnic groups (eg, South Asians, other Asians, and Africans), develop diabetes a decade earlier and at a lower body mass index than Whites, have prominent abdominal obesity, and accelerated the conversion from prediabetes to diabetes. The burden of complications, both macro- and microvascular, is substantial, but also varies according to populations. The syndemics of diabetes with HIV or tuberculosis are prevalent in many developing countries and predispose to each other. Screening for diabetes in large populations living in diverse habitats may not be cost-effective, but targeted high-risk screening may have a place. The cost of diagnostic tests and scarcity of health manpower pose substantial hurdles in the diagnosis and monitoring of patients. Efforts for prevention remain rudimentary in most developing countries. The quality of care is largely poor; hence, a substantial number of patients do not achieve treatment goals. This is further amplified by a delay in seeking treatment, “fatalistic attitudes”, high cost and non-availability of drugs and insulins. To counter these numerous challenges, a renewed political commitment and mandate for health promotion and disease prevention are urgently needed. Several low-cost innovative approaches have been trialed with encouraging outcomes, including training and deployment of non-medical allied health professionals and the use of mobile phones and telemedicine to deliver simple health messages for the prevention and management of T2D.